Molecular characterization of ubiquitin‐specific protease 18 reveals substrate specificity for interferon‐stimulated gene 15. (3rd March 2014) - Basters, Anja; Geurink, Paul P.; El Oualid, Farid; Ketscher, Lars; Casutt, Marco S.; Krause, Eberhard; Ovaa, Huib; Knobeloch, Klaus‐Peter; Fritz, Günter
<x xml:space="preserve">Abstract</x> Protein modification by interferon‐stimulated gene 15 (ISG15), an ubiquitin‐like modifier, affects multiple cellular functions and represents one of the major antiviral effector systems. Covalent linkage of ISG15 to proteins was previously reported to be counteracted by ubiquitin‐specific protease 18 (USP18). To date, analysis of the molecular properties of USP18 was hampered by low expression yields and impaired solubility. We established high‐yield expression of USP18 in insect cells and purified the protease to homogeneity. USP18 binds with high affinity to ISG15, as shown by microscale thermophoresis with a Kd of 1.3 ± 0.2 μm. The catalytic properties of USP18 were characterized by a novel assay using ISG15 fused to a fluorophore via an isopeptide bond, giving a Km of 4.6 ± 0.2 μm and a kcat of 0.23 ± 0.004 s−1, respectively, at pH 7.5. Furthermore, the recombinant enzyme cleaves efficiently ISG15 but not ubiquitin from endogenous cellular substrates. In line with these data, USP18 exhibited neither cross‐reactivity with an ubiquitin isopeptide fluorophore substrate, nor with a ubiquitin vinyl sulfone, showing that the enzyme is specific for ISG15. Structured digital abstract ●ISG15 and USP18 bind by microscale thermophoresis (View interaction) ●USP18 cleaves ISG15 by enzymatic study (View interaction)